LIN28B promotes the progression of endometrial cancer through upregulating MYC and correlates with immune microenvironment - Diao, Yuchao; Li, Xiangkun; Wang, Chang; Jiao, Jinwen; Gao, Dongmei; Mao, Weifang; Yu, Xinping; Yang, Hongjuan (Frontiers in Oncology, 2025)
BackgroundEndometrial cancer (EC), a leading gynecologic malignancy, demonstrates a rising global incidence that imposes significant clinical and socioeconomic burdens. While the RNA-binding protein LIN28B has been reported to promote the progression of EC, its mechanistic role in driving tumor progression and immune modulation remains poorly characterized. This study specifically investigates whether LIN28B promotes EC progression through MYC upregulation and its influence on tumor immune microenvironment remodeling.MethodsUtilizing integrated bioinformatics analysis of TCGA/GTEx datasets and immunohistochemical staining of clinical specimens, we evaluated LIN28B expression in EC. Survival outcomes associated with LIN28B were analyzed using the Kaplan-Meier methodology. Functional validation was conducted in HEC-1A, HEC-1B, and KLE cell lines through siRNA-mediated LIN28B knockdown. Proliferative capacity (CCK-8 and EdU assays), clonogenic potential (colony formation assay), and metastatic behavior (Transwell assays) were systematically assessed. Mechanistic studies employed quantitative real-time PCR and Western blotting to confirm LIN28B-mediated regulation of MYC, with further validation via rescue experiments combining LIN28B overexpression and MYC silencing. Immune microenvironment alterations linked to LIN28B expression were profiled using ssGSEA implemented via the GSVA package. Finally, a multivariate prognostic nomogram incorporating LIN28B expression and clinicopathological parameters was constructed and calibrated using Cox regression modeling and calibration curves.ResultsLIN28B exhibited significant overexpression in EC tissues and was associated with diminished overall survival, progression-free survival, and disease-specific survival. Functional analyses revealed that LIN28B knockdown markedly suppressed EC cell proliferation, migration, and invasion, concurrent with MYC downregulation. MYC depletion abrogated LIN28B-driven oncogenic effects, validating their functional dependency. Immune profiling identified that elevated LIN28B expression correlated with reduced infiltration of thirteen distinct immune cell subsets. A multivariate prognostic nomogram combining LIN28B expression and clinicopathological parameters established a robust predictive model for EC outcomes.ConclusionLIN28B exhibits oncogenic roles in EC by facilitating MYC-mediated tumor progression and modulating the immune microenvironment, establishing its potential as both a therapeutic target and a prognostic biomarker.